Yellow River's Contribution to the Building of Yangtze Delta During the Last 500 Years ‐ Evidence From Detrital Zircon U‐Pb Geochronology - Shang, Yuan; Nian, Xiaomei; Zhang, Weiguo; Wang, Feng (Geophysical research letters, 2021)
The Yangtze Delta (YD), as one of the world mega deltas, its formation process has long been the subject of research. Previous study has proposed a remote connection of the Yellow River (YR) to the building of the YD over the past 600–400 years. However, complex source‐sink routing system of the YD sediment and lack of diagnostic provenance tools have hampered further understanding of this process. Inferred from detrital zircon U‐Pb geochronology, this study revealed an increased and significant contribution of the reworked YR sediment to the YD (up to 26%) since ca. 500 a during the period YR shifted its lower courses and entered the southern Yellow Sea. This study not only highlights the impact of human activity on the formation of the world's large delta but also addresses the intricate interplay between neighboring deltas through marine dynamics, for example, alongshore and tidal currents. Plain Language Summary China's two mega rivers, the Yangtze River and Yellow River have carried tremendous amount of sediments from the Asian inland to the marginal seas. It was widely acknowledged that the Yangtze Delta mainly consists of the sediments derived from the Yangtze River. However, the Yangtze Delta has experienced rapid growth over the past 2000 years and some studies argued that the Yellow River exerts an influence on the building of the Yangtze Delta. Here we used zircon U‐Pb age as “DNA” for the sediment to identify the Yellow River's source signature in the Yangtze Delta and further quantitatively estimated the relative contribution of the Yellow River to the Yangtze Delta. We prove that zircon U‐Pb chronology is a powerful tool in distinguishing Yellow River and Yangtze River sediment and suggest it was the human‐induced southward shift of the Yellow River that provided an additional source for the Yangtze Delta over the past 500 years. Marine dynamics such as tides and alongshore currents were mainly responsible for sediment transport and deposition in the Yangtze Delta. Key Points Detrital Zircon U‐Pb chronology is an effective tool in distinguishing Yellow River and Yangtze River sourced sediments Yellow River derived sediments contributed to the building of Yangtze Delta over the past 500 years as evidenced by zircon U‐Pb ages Human induced Yellow River southward shift provided additional sediment to Yangtze Delta and alongshore current responsible for transport